The relationships between fears, phobias, anxiety on self-identity - Terletska, Larysa; Kukhar, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
According to the aim (to identify the features of the connection of fears, phobias, anxiety with self-esteem of adolescence), an empirical study was conducted, in which the respondents were representatives of school and student youth, namely 120 people: 60 students of 10-11 grades (15-17 years) of Vyshhorod comprehensive school №2 and №3. This sample was chosen not by chance. After all, it is in adolescence is the active development and formation of all components of self-awareness, including self-esteem. According to the age periodization of M. Savchyn and L. Vasylenko, adolescence is divided into two groups: representatives of early youth (15-18 years) and late youth (18-23 years) or senior school and student age. The presented study covers only certain aspects of such a complex phenomenon as self-assessment. As its subject was the socio-psychological features of self-attitude of adolescents and young people, other social and age categories, as well as socio-psychological factors influencing the features of self-attitude, in particular: financial status, degree of self-realization and more. The study of this problem requires further comprehensive research, because adequate positive self-attitude is the most optimal for the formation and development of personality, determines the achievement of its inner harmony. In our further study of self-assessment, a promising direction, in our opinion, is to clarify the features of this phenomenon in other age groups. Consideration of the influence of gender on the peculiarities of self-assessment, in this perspective, will be useful in both theoretical and practical aspects.